2013
DOI: 10.1111/wrr.12043
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 reduces scar formation in both animal and human cutaneous wounds: Results of two preclinical and phase II randomized control studies

Abstract: Cutaneous scarring affects up to 100 million people per annum. There is no effective scar reducing/preventing therapeutic developed to date. Interleukin (IL)-10 is an anti-inflammatory and antifibrotic cytokine. In the embryo it is important for scarless wound repair. We investigated the effect on wound healing and scarring of a double deletion of the IL-10 and IL-4 genes in a knockout (KO) mouse model, and also the effect of exogenous addition of recombinant human (rh) IL-10 into rat and human cutaneous incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 23 publications
4
91
0
1
Order By: Relevance
“…Known pleiotrophy of certain cytokines in salvaged blood, such as IL-17A, IFN-γ and TNF-α, could have facilitated regenerative rather than proinflammatory processes, as they would have facilitated synthesis of the chemokines MCP-1/CCL2, MIP-1α/CCL3 and IL-8/CXCL8 [47]. Moreover, IL-9 and IL-10 would have facilitated wound healing by suppressing autoinflammatory reactions and excessive scarring [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Known pleiotrophy of certain cytokines in salvaged blood, such as IL-17A, IFN-γ and TNF-α, could have facilitated regenerative rather than proinflammatory processes, as they would have facilitated synthesis of the chemokines MCP-1/CCL2, MIP-1α/CCL3 and IL-8/CXCL8 [47]. Moreover, IL-9 and IL-10 would have facilitated wound healing by suppressing autoinflammatory reactions and excessive scarring [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…This brief exposure has led to the development of clinical trials to further investigate recombinant IL-10 as a potential therapeutic agent, thereby eliminating delivery of viral components. 49 Although there have been promising results with decreased scar formation noted at twelve months in a randomized, double-blinded, placebo controlled trial, further studies are needed before a clinically relevant product will be available.…”
Section: Il-10 As a Therapeutic Agentmentioning
confidence: 99%
“…110 Recently, 2 murine studies and a phase II randomized controlled trial in humans have confirmed the importance of IL-10 in reducing inflammation, accelerating wound healing, and reducing scarring with the use of exogenous recombinant human IL-10 application to cutaneous incisions, suggesting that rhIL-10 may be a new class of therapeutic options for scar minimization. 111 …”
Section: Interleukin-10mentioning
confidence: 99%